Protocol for the development of a procedure guide on Laparoscopic Cholecystectomy: Beyond bile duct injury prevention - Camilo Ramírez-Giraldo; Daniela Álvarez-León; Alejandro Karduss-López (PLoS ONE, 2026)
Background Laparoscopic cholecystectomy is one of the most frequently performed operations worldwide and the standard treatment for benign gallbladder disease. Although several “safe cholecystectomy” initiatives aim to prevent bile duct injury, current guidelines do not comprehensively address the intraoperative technical conduct of the procedure. Key elements—including exposure, dissection techniques, technical sequencing, and intraoperative decision-making—remain inconsistently defined. This protocol describes the development of an evidence-based, globally applicable clinical procedure guideline intended to standardize technical performance, enhance patient safety, and support surgical training and quality improvement. Methods The guideline will be developed following AGREE II standards to ensure methodological rigor, transparency, and stakeholder involvement. The Guideline Development Group comprises coordinators, a steering committee, and multidisciplinary experts from surgical societies and academic institutions. Clinical questions will be generated using the PICO framework and refined through a Delphi consensus process following the ACCORD guideline. For each question, systematic literature searches will be conducted in accordance with PRISMA standards. When feasible, evidence will be synthesized using pairwise or network meta-analysis (PRISMA-NMA, PRISMA-Search); when quantitative synthesis is not possible, findings will be summarized narratively using SWiM guidance. Study selection, data extraction, and risk-of-bias assessment will be performed independently using validated tools (ROB 2.0, ROBINS-I, AMSTAR-2), with search management in Rayyan®. Recommendations will be developed using the GRADE approach, with evidence profiles created in GRADEpro GDT. A second Delphi process will be conducted to reach consensus on each recommendation, applying predefined thresholds for participation and agreement. Discussion This guideline seeks to fill a critical gap in the technical standardization of laparoscopic cholecystectomy by providing a comprehensive, evidence-based framework that extends beyond bile duct injury prevention. Existing guidelines lack methodological rigor and fail to address key intraoperative elements such as exposure, dissection strategies, and decision-making. Through systematic evidence synthesis and consensus processes, this project aims to harmonize global surgical practice and establish a benchmark for training, safety, and quality improvement. Registration This protocol was prospectively registered in the Open Science Framework on December 18, 2025 ( https://doi.org/10.17605/OSF.IO/78QSE ).